(untitled) (IITM Journal of Business Studies, 2024)
This study explores the relationship between workplace ostracism and workplace behavior, with a focus on how neuroticism moderates this relationship. Data from 100 employees in private firms in India were analyzed using PLS SEM. Results indicate that workplace ostracism negatively impacts job performance but not deviant behavior. Neuroticism has a stronger moderating effect on the link between workplace ostracism and job performance but does not affect deviant behavior. The study contributes to existing knowledge by examining the moderating effect of neuroticism on workplace exclusion.